Whistle‐blowing in the digital era: motives, issues and recommendations. (29th April 2019) - Lam, Helen; Harcourt, Mark
Abstract : With the ever‐increasing popularity of social media, whistle‐blowing, which generally refers to the disclosure of organisational wrongdoing, has entered a new era. Whistle‐blowing via virtual platforms has transformed not just the channel of disclosure, but also the associated motives, processes and outcomes. The impact on the whistle‐blower, the organisation and the public can often be accelerated and is seen as being more significant than traditional whistle‐blowing through internal means or external dedicated authorities or journalists. Yet systematic research on this changing phenomenon is just emerging, and regulation (e.g. for rewards, safeguards or protection) is lagging behind. In this paper, we specifically examine the impetus, as well as the benefits and drawbacks, of using online channels such as social media, blogging or websites, for whistle‐blowing by both employees and non‐employees, taking into consideration recent case law and development. A number of recommendations are proposed for virtual whistle‐blowers, organisations and governments.